Assessment of Elderly Type 2 Diabetic Patients who Self-adjust Their Insulin Regimen in Al-Qassim Region - Alharbi, Mariam S.; Alrashidi, Turki; Al-Harbi, Moath Saleh; Al Zahrani, Essa; Alkahlot, Mohammed H.; Aljaberi, Mohammed S (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a multifactorial chronic disease. To avoid long-term and short-term complications, good glycemic control must be achieved. The majority of T2DM patients who require insulin therapy have their doses modified by their physicians; this procedure takes time and may not result in the optimal glycemic control. AIM: This study aims to ascertain whether elderly T2DM patients in Al-Qassim region modify their own insulin regimen and its effect on their glycemic control. METHODS: This cross-sectional study was conducted in Al-Qassim University Medical City and Diabetic Centers in Buraydah, Saudi Arabia. Data were collected using a questionnaire. RESULTS: A total of 384 participants were enrolled with a mean age of 70.2 ± 6.0 (61–94) years, majority (53.6%) of whom were females. About half (50.8%) were not educated and two-third (66.1%) giving insulin injections by themselves. Less than half (40.6%) of the participants changed their insulin dose, out of which 8.3% changed the dose by themselves. The mean hemoglobin A1C (HbA1c) level was 8.8 ± 1.9 with a range of 5.2–17. About 30.5% had recent hypoglycemic attacks, majority (47.9%) of whom had only one episode. Diabetic complications were seen among 127 participants with retinopathy as the most common (43.3%) complication. Hypoglycemic attacks and insulin dose adjusting were not found to be significantly associated (p = 0.476). The last HbA1c level was found to be significantly associated with adjusting insulin dose. CONCLUSION: Self-adjusting insulin dose was found to be rare. Moreover, HbA1c in patients who self-adjust their insulin dose was found to be significantly lower.